PERKAWINAN LESBIAN, GAY, BISEKSUAL DAN TRANSGENDER/TRANSEKSUAL (LGBT) PERSPEKTIF HUKUM ISLAM - Rohmawati, R. (Ahkam: Jurnal Hukum Islam, 2016)
The marriage between transgender, lesbian, gay, bisexual couple has become the most discussed-public issues. The rising interest on this issue is due to the more open access to the information, free expression right, and human rights. In the past, the marriage between those couples was done under cover. Today, such a marriage is not a taboo anymore. The pros and the contras arise. From the perspective of Islamic law, the marriage between transgender, lesbian, gay, and bisexual couples is forbidden because it is against the civilized norms of family settlement guided through the transcendental divine of the Quran and Hadis. Such a marriage is a threat to the existence of the essential human nobility because it will devastate human origins, thought, and soul. Kata Kunci: LGBT, Hukum Islam